Pacifying Russia: International Aid and NATO Expansion - Wendlandt, Astrid (Tufts Archival Research Center, 2005)
Volume 22, Issue 2. Summer/Fall NATO's present and future expansion has served to demonstrate the extent to which it is tied to other world policy issues and how Russia's influence over these issues has become relatively limited.